The modulation of emotional memory consolidation by dream affect - du Plessis, Liëtte; Lipinska, Gosia (Frontiers in Sleep, 2023)
Introduction. Research in the field of cognitive neuroscience has focused on the role of sleep in various neurocognitive processes such as memory consolidation. However, an area that has not been adequately researched is the role of dreaming in this memory process. This study aimed to determine the relationship between affect experienced in dreams and emotional memory consolidation. Considering that REM dreams are laden with emotion and that emotion enhances memory, one possibility is that dream affect could also play a role in emotional memory consolidation. We hypothesised that greater dream-related affect would be associated with greater memory retention of emotional but not neutral information. Methods. 126 healthy participants, aged 18 -35, were recruited for the online study, of which 103 participants had valid data (female: n =73). On the night of the study, participants viewed a series of pictures from the South African Affective Picture System (SA-APS) in an online session. Afterwards, they verbally recalled as many pictures as possible. The following morning, they were asked to recall any dreams and rate the emotional intensity of their dreams. Participants then again verbally recalled all the pictures that they could remember from the previous night. Results. Contrary to the prediction, dream-related affect, regardless of valence, did not predict memory consolidation of positive or negative information. Instead, increases in dream-related affect, and especially anxiety were predictive of better memory retention of all information. The findings also showed that an increase in negative affect in dreams predicted better memory retention of negative information. Discussion. Our results suggest that dream affect is an important modulator of memory consolidation processes occurring during sleep. Furthermore, increased negative affect may indicate which experiences are salient and require consolidation to form long-lasting memories that can guide future behaviour. Conclusion. These findings have implications for psychiatric disorders, such as major depression, which is characterised by negative affect and increased memory sensitivity to negative stimuli.